Towards Consistency and Transparency in Academic Integrity - Razi, Salim; Glendinning, Irene; Foltýnek, Tomáš (Peter Lang International Academic Publishing Group, 2018)
This book is an outcome of the 4th International Conference «Plagiarism across Europe and Beyond» organized by Canakkale Onsekiz Mart University, Mendel University in Brno, and the European Network for Academic Integrity. The conference is co-funded by the Erasmus+ Strategic Partnerships Programme of the European Union. It aims to be a forum for sharing best practices and experiences by addressing issues of academic integrity from a wide-scope global perspective. With regards to the crucial role of ethics and honesty in academic work, universities are in need of more effective policies against infringements of academic standards. The papers in this book therefore aim to contribute to the standardization of consistent and transparent approaches to issues of academic integrity from several perspectives.